RobotX: development of surface vehicle's shooting system of balls - Tsoi, Chee Chung (Nanyang Technological University, 2024)
The aim of this final year project is the development of the shooting system of balls of the Wave Adaptive Modular Vessel (WAM-V) Unmanned Surface Vehicle (USV) as part of the overall Autonomous Maritime System (AMS) used by Nanyang Technological University to compete in the Maritime RobotX Challenge 2024. The shooting system will provide the technical equipment capabilities for the AMS to complete Task 6: Dock and Deliver which involves flinging racquetballs into holes to score points. This report outlines the project deliverable as the base guidance platform component of the shooting system to provide motorised 2-degrees-of-freedom control (yaw and pitch) over the balls being launched. Similar robotics projects and applications are surveyed to support the conceptualization process, design considerations, and mechanical features, and various challenges faced as well as solutions implemented to optimize the overall design outcome are discussed. After the manufacturing and assembly, the mechanical components are tested and verified against the initial performance projections. The strengths and weaknesses of the design are analysed before several optimisation modifications are proposed and implemented. The project concludes by discussing the future works to integrate the platform into the overall shooting system and AMS.